Self-assessed hearing handicap in the elderly: a pilot study on Iranian population - Fatemeh Heidari (Auditory and Vestibular Research, 2021)
Background and Aim: Presbycusis is a prevalent chronic condition in the elderly which may have potential adverse effects on social and emotional aspects of their life. There is no one to one relationship between audiogram and the perceived handicap in elderly. A good way to measure hearing handicap are self-assessment tools. This study was aimed to translate, adapt and establish face validity of Short form of Hearing Handicap Inventory for the Elderly (HHIE-S) and the correlation with pure-tone and speech audiometry results as well as score of the other self-assessmnet tool (Self-Assessment of Communication: SAC) in the Iranian elderly. Methods: HHIE-S was translated into Persian and face validity was established.  It was administered in 80 elderly participants. Correlation of their scores with their pure tone averages of 3 and 4 frequencies (PTA0.5-1-2 and PTA0.5-1-2-4), word recognition score (WRS) in quiet, and SAC scores was determined. Results: The experts mean scores to PHHIE-S was 99.63%. There were significant correlations between PHHIE-S with SAC (r = 0.89; p < 0.001), PTA0.5-1-2 (r = 0.4; p < 0.001), PTA0.5-1-2-4 (r = 0.6; p <0.001) and WRS (r = -0.4; p < 0.001). There was no significant gender effect on any of the measures (p > 0.05). Conclusion: Simply evaluation of the hearing levels is not adequate in elderly. Self-assessment tools can shed light on the specific disability induced by hearing loss. PHHIE-S appears to be an easy and fast tool that may helpful to distinguish patients who might need rehabilitative services.